TEORI PERKEMBANGAN MORAL DAN MODEL PENDIDIKAN MORAL - Agus Abdul Rahman (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2010)
Moral values and it’s decadence were one of many problems that in Indonesia, whereas becoming a huge responsibility that hold by all member of society. The inquiry, designing and implementation of moral education strategy is foreseen as the most important aspect to improve society. Aside from great efforts to improve society, it is imperative that we also need to review and inquire more about moral development theory. Nowadays, it seems that moral development theory had moved from its role and position which moved from its autonomic, rationalistic and universalistic nature to more emotionally roles and becoming more culture bounded. The changes in society paradigm were also have many implications on education of moral development. In this paper there are at least 3 models that can be used in moral education, which are the learning of rule ethics, character ethics and the integration of both in multidimensional fields.